Measuring the Preservice Counselor’s belief-diagnostic competence: A Reflective Practice Experience from Peer Evaluation - Husni Hanafi; M. Ramli; IM Hambali; Rizka Apriani; Nanda Alfan Kurniawan (JKI (Jurnal Konseling Indonesia), 2025)
Belief diagnostic is one of the main competence during the cogntiive assessment within cognitive counseling, inluding the Rational Emotive Behavior (REB) counseling. This study aims to measure and explore the preservice counselor belief-diagnostic and refelctive practice during the course and training. This study used the mixed method and involving 40 preservice counselors within four sessions. Repeated measurement used to conduct the experience by having the role of counselor, counselee, and vice-versa. Structured observation and reflection using belief-diagnostic instruments and analyzed use of descriptive anlysis both in numbers and words based on the notes from both. The resuts indicate the improvements of belief-diagnostic competence for diagnostic accuracy and reflective depth from the first into fourth sessions in general. The strongest gain indicate in conceptual differentiation of the irrational beleifs. Specifically, a slight perfromace dips occurred within the fourth sessions. The belief-diagnostic reasoning and interpretative reflective practice had been reached the high score with general upward trends. This study suggest to evluate the overall performance to gain broader reflective practice. Another suggestions might led to research design of longitudinal or multiple single subject design to gain deeper exploration of preservice counselor professional growth.